Enhanced Tribological Properties of Nanolubricants with Multiwalled Carbon Nanotube Additives - Demirkol, Metehan; Kucukyildirim, Bedri Onur (AMER SOC TESTING MATERIALS, 2024)
This study aims to achieve novel tribological properties by utilizing industrial-type multiwalled carbon nanotubes (MWCNTs) as lubrication additives in 20W-50 engine oil, in parts per million (ppm). Nanolubricants consisting of various amounts of MWCNTs were prepared and subjected to ball-on-disk tests to observe tribological characteristics. For ball-on-disk tests, friction coefficient data were obtained during testing, whereas wear characteristics were achieved from test samples through imaging and processing methods. Spectroscopic analyses were done to collect additional data about the existence of MWCNTs on the friction surfaces. The data acquired were analyzed according to theoretical bases. It has been found that the best results as antiwear properties are obtained at 600-ppm MWCNT addition by a wear decrease of 81.02 % and decreased severity of wear tracks, where antifriction characteristics were found to be enhanced at 200 ppm by a friction coefficient decrease of 8.07 %. However, 600-ppm MWCNT addition also constitutes a limit value whereby further addition can cause an increase in the wear of friction pairs. It has been shown that MWCNTs can enhance antifriction and antiwear properties even in ppm-level amounts, which can be considered as lower amounts of nanoadditives when compared to the literature and can present economically suitable lubrication solutions.
Keywords: carbon nanotube; nanolubricant; wear; friction; MECHANICAL-PROPERTIES; DRY FRICTION; COMPOSITES; BEHAVIOR; VISCOSITY; ALUMINUM; GRAPHENE; MWCNT; STEEL; Materials Science